Comparative and population mitogenomic analyses of Madagascar's extinct, giant 'subfossil' lemurs. Issue 79 (February 2015) - Kistler, Logan; Ratan, Aakrosh; Godfrey, Laurie R.; Crowley, Brooke E.; Hughes, Cris E.; Lei, Runhua; Cui, Yinqiu; Wood, Mindy L.; Muldoon, Kathleen M.; Andriamialison, Haingoson; McGraw, John J.; Tomsho, Lynn P.; et al.
Abstract: Humans first arrived on Madagascar only a few thousand years ago. Subsequent habitat destruction and hunting activities have had significant impacts on the island's biodiversity, including the extinction of megafauna. For example, we know of 17 recently extinct 'subfossil' lemur species, all of which were substantially larger (body mass ∼11–160 kg) than any living population of the ∼100 extant lemur species (largest body mass ∼6.8 kg). We used ancient DNA and genomic methods to study subfossil lemur extinction biology and update our understanding of extant lemur conservation risk factors by i) reconstructing a comprehensive phylogeny of extinct and extant lemurs, and ii) testing whether low genetic diversity is associated with body size and extinction risk. We recovered complete or near-complete mitochondrial genomes from five subfossil lemur taxa, and generated sequence data from population samples of two extinct and eight extant lemur species. Phylogenetic comparisons resolved prior taxonomic uncertainties and confirmed that the extinct subfossil species did not comprise a single clade. Genetic diversity estimates for the two sampled extinct species were relatively low, suggesting small historical population sizes. Low genetic diversity and small population sizes are both risk factors that would have rendered giant lemurs especially susceptible to extinction. Surprisingly, among the extant lemurs, we did not observe a relationship between body size and genetic diversity. The decoupling of these variables suggests that risk factors other than body size may have as much or more meaning for establishing future lemur conservation priorities.